What Do Teachers Think About AI? An Empirical Study Based on the TPU-AIED-Q - Silva, Thomaz Edson Veloso da; Lima, André Araújo de; Veloso, Ronathan Nascimento (Anais do Workshop de Informática na Escola (WIE), 2025)
This study investigates Brazilian teachers’ perceptions of Artificial Intelligence (AI) in education using the TPU-AIED-Q instrument. Results from 143 respondents show generally positive attitudes, especially regarding AI’s impact on educational practices. Moderate concerns about ethical risks and limited AI knowledge were also observed. No significant differences were found across gender, institution type, age, or experience. The findings highlight the need for inclusive teacher training and policy initiatives to support critical and informed AI integration in schools.